Theoretical Problems of Physical Education and Sport - Norboyevich, Odilov Otabek (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the current problems of physical education and sport. Also, recommendations are given based on research to further improve and develop the industry.